Uji Aktivitas Antibakteri Ekstrak Metanol, Ekstrak Fraksi N-Heksan dan Ekstrak N-Heksan Daun Filicium decipiens terhadap Bakteri Staphylococcus aureus dan Bakteri Bacillus subtilis (Universitas Kristen Maranatha, 2020)
The previous study shows ethanol extract of Filicium decipiens leaf possesses a strong antibacterial activity against Staphylococcus aureus, but there have been no studies of the antibacterial activity with different solvents. The purpose of this study was to determine the antibacterial activities of methanol, n-hexane fraction of methanol and n-hexane extract of F. decipiens leaves against S. aureus and Bacillus subtilis bacteria. Extraction was carried out by soxletation method using methanol and n-hexane solvent. The antibacterial activity test was done by measuring the minimum inhibitory concentration (MIC) and Zone of Inhibition. The results showed that methanol extract did not have activity either against S. aureus bacteria or against B. subtilis. N-hexane extract which was fractionated from methanol extract had no activity against B. subtilis but showed moderate activity against S. aureus with 9 mm inhibition diameter at an extract concentration of 40%. N-hexane extract has very strong antibacterial activity against S. aureus with inhibition diameter reaching 21 mm at extract concentration of 30% and showing strong activity against B. subtilis bacteria with inhibition diameter of 10 mm at extract concentration of 30%. It can be concluded that n-hexane extract from F. decipiens has a potent as natural antibiotic material. Keywords: Filicium decipiens; Staphylococcus aureus; Bacillus subtilis; n-hexane extract; methanol extract